Manifestaciones cutáneas de enfermedades gastrointestinales - Tapia T., Gabriela; Martínez L., Cristina; Vera G., Valentina; Calderón H., Perla; Poniachik T., Jaime (Revista Hospital Clínico Universidad de Chile, 2018)
The gastrointestinal system is closely related to the skin. Multiple disorders of the gastrointestinaltract that manifest clinically on the skin surface are recognized, which can even occur beforeestablishing the definitive diagnosis of the disease. For this reason, it is necessary that thedermatologist is internalized regarding the wide variety of clinical signs that can guide theetiological study, which requires in most cases, a multidisciplinary management.